Perlindungan hukum kepada pekerja atas pengabaian ganti Rugi dalam pemutusan kontrak kerja - Bangapadang, Mona Yulianty; Franciska, Wira; Hutomo, Putra (CENDEKIA : Jurnal Penelitian dan Pengkajian Ilmiah, 2025)
In the provisions of Article 62 of Law Number 13 of 2003 concerning Manpower, it regulates the provision of compensation for termination of employment contracts. In practice, companies do not provide compensation to workers whose employment relationships are terminated in violation of labor law regulations. This is certainly detrimental to workers. The method used in this research is normative juridical research.  The research results show that legal protection for employees for non-payment of compensation in the termination of employment contracts is in the form of repressive legal protection, namely that workers have the right to take legal action through litigation or non-litigation, namely in the form of Bipatrit, Tripartite and filing a lawsuit with the Industrial Relations Court, workers can even file an execution against the decision of the Industrial Relations Court.